Delayed separation of the umbilical cord, severe widespread infections, and immunodeficiency. Issue 5 (May 1981) - Bissenden, J G; Haeney, M R; Tarlow, M J; Thompson, R A
Abstract : Three of 4 children in a family died from infection before age one year. All 3 had delayed separation of the umbilical cord in the third week. One child was found to have defects both in specific antibody production and in neutrophil function; these were not improved by treatment with ascorbic acid or levamisole.